Analisis Yuridis Pertimbangan Hakim dalam Putusan Bebas Tindak Pidana Pertambangan Tanpa Izin: Studi Putusan No. 57/Pid.Sus/2023/PN Koba - Askaria Askaria; Muhamad Adystia Sunggara; Enny Agustina (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
The acquittal in the case of illegal mining offenses is an interesting phenomenon to examine, as it reveals differing interpretations of the element “not originating from a holder of an IUP (Mining Business Permit)” as stipulated in Article 161 of Law No. 3 of 2020 on Mineral and Coal Mining. These differing interpretations create uncertainty in the application of the law, especially when judges approach the meaning of mining business permits in distinct ways. This study aims to analyze the legal considerations made by the judge in Decision No. 57/Pid.Sus/2023/PN Koba and assess its alignment with the principle of legal certainty in the context of law enforcement in the mining sector. Although legally valid, the acquittal raises concerns about the effectiveness of law enforcement in the mining sector, as well as the application of the burden of proof in similar cases. The research method used is a normative juridical approach with a case study (case approach), examining the applicable regulations related to mining and the legal principles applied in court decisions. Primary legal materials consist of relevant legislation and court decisions, while secondary legal materials include legal literature, scholarly articles, and previous relevant research. The analysis is conducted descriptively and qualitatively, focusing on the interpretation of the elements of the crime and the application of legal principles by the judge in delivering the acquittal. The research findings show that the panel of judges interpreted the element “not originating from a holder of an IUP” in a formalistic manner, focusing on proving the ownership of the mining permit without tracing the origin of the mined materials. This narrow interpretation led to the defendant’s acquittal, as the defendant was not proven formally to be involved in illegal mining, making this decision legally justified. While this reasoning aligns with the principle of in dubio pro reo (when in doubt, acquit), substantively it fails to reflect a balance between the protection of individual rights and the state's interests in natural resources. Therefore, there is a need for harmonization between the interpretation of criminal elements, the burden of proof, and the application of criminal sanctions in mining cases, to ensure future court decisions provide fair, consistent, and legally certain rulings in line with the objectives of national law enforcement and to effectively punish those engaging in illegal mining.